Pentingnya Menjaga Kesehatan Jiwa saat Pandemi Covid 19 - Dwi Kartika Pebrianti; Armina Armina (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The case of the Corona Virus is known through a mysterious disease that paralyzed the City of Wuhan, China. The tragedy at the end of 2019 has continued until the spread of the Corona virus has spread throughout the world. Quoted from CNN, here are some things that must be known about the development of the Corona virus, which is commonly called the Corona virus or COVID-19, until it broke out and became a pandemic. Everyone needs to maintain mental health to avoid physical complaints that arise due to stress. Because when someone is stressed, the immune system in the body will decrease. This will cause the body to be susceptible to disease. Realizing that anxiety due to COVID-19 has pervaded many communities, the World Health Organization (WHO) in March 2020 released a guide for people to jointly maintain mental health. Through community service activities by directly interacting with the community while still implementing the COVID-19 protocol, socialization was carried out about the importance of maintaining mental health in the community during the Covid-19 Pandemic. Community service at RT 30 Recognize Besar, the community can know, recognize and overcome how to recognize mental health disorders including anxiety and depression, it is hoped that the community will always think optimistically in facing the Covid-19 pandemic, by implementing health protocols, maintaining a healthy lifestyle, regular exercise, always think positively, maintain communication with family and friends